21st Century Futurama: Contemplating Removal of Urban Freeways in the World of Tomorrow - Jessica Kraft-Klehm (Washington University Journal of Law & Policy, 2015)
Urban freeway removal has been increasing in popularity due to its viability as a mechanism for positive urban development, as it is thought to spur economic development and the revitalization of many ‘downtown’ areas that have been blighted by an unfair system. This Note discusses the Federal-Aid Highway Act and its impact on urban America. Ultimately, this note proposes that national transportation policy be revised to actively promote urban freeway removal projects.
Keywords: transportation policy; freeway; urban revitalization